Implementasi Peraturan Daerah Nomor 3 Tahun 2019 Tentang Rencana Pembangunan Dan Pengembangan Perumahan Dan Kawasan Pemukiman Di Kota Bontang (Studi Kasus Kawasan Kumuh di Pesisir Kota Bontang) - Farhan Eka Setiawan Haris; Muhammad Jamal; Budiman (Jurnal Ilmu Pemerintahan, 2023)
This study aims to determine the extent to which Bontang City Regional Regulation No. 03 of 2019 has been implemented to address slum areas in Bontang City. In this study there is a formulation of the problem, namely how to implement the implementation of the Regional Regulation No. policy. 3 of 2019 concerning Plans for Development and Development of Housing and Residential Areas in the City of Bontang.This study used a qualitative approach with a case study method on several research subjects including the community, the Bontang City Lurah, and the Bontang City Housing and Agriculture Office. Data collection was carried out by means of observation, documentation study, interviews, literacy studies and field notes, then data analysis was carried out using data reduction, data presentation, triangulation and drawing conclusions.